Solar Selective Absorber Coating with Ag Infrared Reflector for Receiver Tubes Operating at 550 °C - Salvatore Esposito; Antonio D’Angelo; Claudia Diletto; Gabriella Rossi; Raffaele Volpe; Antonio Guglielmo; Anna De Girolamo Del Mauro; Claudia Prestigiacomo; Michela Lanchi (Energies)
The present work introduces a new solar selective absorber coating (SSAC) for the receiver tube of Concentrated Solar Power (CSP) systems, proposing silver as an infrared reflector for application at 550 °C. In the past, the Italian National Agency for New Technologies, Energy and Sustainable Economic Development (ENEA) has developed SSACs suitable for applications at 550 °C, featuring solar absorbers based on graded multilayer cermet of WN-AlN and W-Al2O3 and an infrared reflector of tungsten. Although these coatings ensured properly stable photothermal performance at 550 °C, due to the low tungsten diffusivity, their hemispherical emittance could be reduced by using metals with higher reflectance in the infrared region, like silver. However, the high diffusivity of silver compromises its use at high temperatures. This last drawback has been addressed by foreseeing two stabilizing layers enclosing the Ag infrared reflector. One W stabilizing layer was placed between the substrate and the Ag infrared reflector, whereas a second stabilizing layer, selected among aluminum nitride deposited with a low and high nitrogen flow and aluminum oxide deposited at a low oxygen flow, was placed between the Ag infrared reflector and the solar absorber. Accelerated aging tests revealed a negligible (not detectable) degradation of the solar absorptance for the new SSACs. Furthermore, the hemispherical emittance at 550 °C increased by 0.75% and 0.42% for solar coatings with aluminum nitride stabilizing layers deposited through a high and low nitrogen flow, respectively. Differently, the increase was evaluated as being equal to 0.08% for the solar coating with an aluminum oxide stabilizing layer deposited through a low oxygen flow. The manufactured solar coating with a stabilizing layer of aluminum nitride deposited with a low nitrogen flow exhibited a solar absorptance of 95%, comparable to ENEA coatings incorporating a W infrared reflector for applications at 550 °C, whereas the estimated hemispherical emittance at 550 °C was 2% lower than that of the best ENEA coating with a W infrared reflector for the same temperature.